Motif Awan (Model Partisipatif Wisatawan) Sebagai Solusi Konservasi Hutan Evergreen di Taman Nasional Bali Barat - Rani, Sri; Murtafiah, Murtafiah; Zakiyah, Neza; Benardi, Andi Irwan (Edu Geography, 2019)
Bali Barat National Park is one of the tourist destinations on the island of Bali which was developed as a place of research, development of science and education, supporting cultivation, tourism, and recreation. The objectives of this article include: (1) knowing the evergreen forest conditions in Bali Barat National Park, (2) knowing the conservation activities that have been carried out, and (3) knowing the contribution of Motif Awan (participatory models of tourists) in maintaining conservation. The research method used is qualitative descriptive with triangulation validity test The results showed that the evergreen forest conditions in Bali Barat National Park were good, there was little damage but not so much. Existing ecosystems can improve themselves. Conservation efforts carried out include security patrols, monitoring of Bali curves, and clean environmental actions. Community involvement in conservation efforts is successful in conservation efforts and provides optimal results. Visitor participation is needed to maintain the Bali Barat National Park area, especially in relation to waste and ecosystem sustainability.